Overcoming methamphetamine withdrawal syndrome through cognitive behavioural therapy in female correctional inmates - Fitri, Khirza Maulida; Widyastuti, Rita Hadi (Universitas Muhammadiyah Semarang, 2021)
Cognitive-behavioural therapy (CBT) approaches have among the highest level of empirical support for drug and alcohol use disorder treatment. The unbearable impact of withdrawal syndrome such as physical related problems, psychological, social and behavioural can take a long-term impact such as affective and anxiety disorder that can lead to depression. CBT as an intervention that improves coping-skill, and strategy to change a maladaptive mindset should be convenient to reduce withdrawal symptoms. The effect of CBT intervention on the severity of the symptoms of methamphetamine withdrawal syndrome is still narrow. This research is aimed to find out the CBT effect on withdrawal symptoms in both qualitative and quantitative methods on female inmates. This research uses a case study design. Data were conducted using Amphetamine Withdrawal Questionnaire (AWQ) before and after CBT intervention. Data were analyzed using univariate analysis presented as distribution frequency on both before and after the intervention and discussed with single case analysis. Â The result showed that CBT affects reducing withdrawal syndrome symptoms severity after 4 weeks and 4 session intervention. CBT affects decreasing withdrawal syndrome severity level. Based on these findings, the correctional nurse needs to develop comprehensive nursing care by providing CBT on a rehabilitation program to decrease female inmatesâ€™ withdrawal syndrome severity level.